Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Cách 1:
\(A=\left(6-\frac{2}{3}+\frac{1}{2}\right)-\left(5+\frac{5}{3}-\frac{3}{2}\right)-\left(3-\frac{7}{3}+\frac{5}{2}\right)\)
\(=\left(\frac{36}{6}-\frac{4}{6}+\frac{3}{6}\right)-\left(\frac{30}{6}+\frac{10}{6}-\frac{9}{6}\right)-\left(\frac{18}{6}-\frac{14}{6}+\frac{15}{6}\right)\)
\(=\frac{35}{6}-\frac{31}{6}-\frac{19}{6}\)
\(=-\frac{15}{6}\)
\(=-\frac{5}{2}\)
Cách 2:
\(A=\left(6-\frac{2}{3}+\frac{1}{2}\right)-\left(5+\frac{5}{3}-\frac{3}{2}\right)-\left(3-\frac{7}{3}+\frac{5}{2}\right)\)
\(=6-\frac{2}{3}+\frac{1}{2}-5-\frac{5}{3}+\frac{3}{2}-3+\frac{7}{3}-\frac{5}{2}\)
\(=\left(6-5-3\right)+\left(-\frac{2}{3}-\frac{5}{3}+\frac{7}{3}\right)+\left(\frac{1}{2}+\frac{3}{2}-\frac{5}{2}\right)\)
\(=-2+0-\frac{1}{2}\)
\(=-\frac{4}{2}-\frac{1}{2}\)
\(=-\frac{5}{2}\)
C1
A=(6−23+12)−(5+53−32)−(3−73+52)=(6.66−2.26+36)−(5.66+5.26−3.36)−(3.66−7.26+5.36)=36−4+36−30+10−96−18−14+156=356−316−196=35−31−196=−156=−52=−212.A=(6−23+12)−(5+53−32)−(3−73+52)=(6.66−2.26+36)−(5.66+5.26−3.36)−(3.66−7.26+5.36)=36−4+36−30+10−96−18−14+156=356−316−196=35−31−196=−156=−52=−212.
C2
A=(6−23+12)−(5+53−32)−(3−73+52)=6−23+12−5−53+32−3+73−52=(6−5−3)+(−23−53+73)+(12+32−52)=−2+−2−5+73+1+3−52=−2+0−12=−52=−212
4. (3/4-81)(3^2/5-81)(3^3/6-81)....(3^6/9-81).....(3^2011/2014-81)
mà 3^6/9-81=0 => (3/4-81)(3^2/5-81)....(3^2011/2014-81)=0
C1: dễ nên tự làm nhé
C2: \(A=\left(6-\frac{2}{3}+\frac{1}{2}\right)-\left(5+\frac{5}{3}-\frac{3}{2}\right)-\left(3-\frac{7}{2}+\frac{5}{2}\right)\)
\(=6-\frac{2}{3}+\frac{1}{2}-5-\frac{5}{3}+\frac{3}{2}-3+\frac{7}{3}-\frac{5}{2}\)
\(=6-5-3+\left(\frac{1}{2}+\frac{3}{2}-\frac{5}{2}\right)-\left(\frac{2}{3}+\frac{5}{3}-\frac{7}{3}\right)\)
\(=-2-\frac{1}{2}=\frac{-4}{2}-\frac{1}{2}=\frac{-5}{2}\)
Cách 1:
A = \(\left(6-\frac{2}{3}+\frac{1}{2}\right)-\left(5+\frac{5}{3}-\frac{3}{2}\right)-\left(3-\frac{7}{3}+\frac{5}{2}\right)\)
A = \(\frac{35}{6}-\frac{31}{6}-\frac{19}{6}\)
A = \(\frac{-15}{6}=\frac{-5}{2}\)
Cách 2:
A = \(\left(6-\frac{2}{3}+\frac{1}{2}\right)-\left(5+\frac{5}{3}-\frac{3}{2}\right)-\left(3-\frac{7}{3}+\frac{5}{2}\right)\)
A = \(6-\frac{2}{3}+\frac{1}{2}-5-\frac{5}{3}+\frac{3}{2}-3+\frac{7}{3}-\frac{5}{2}\)
A = \(6-5-3-\frac{2}{3}-\frac{5}{3}+\frac{7}{3}+\frac{1}{2}+\frac{3}{2}-\frac{5}{2}\)
A = \(\left(6-5-3\right)-\left(\frac{2}{3}+\frac{5}{3}-\frac{7}{3}\right)+\left(\frac{1}{2}-\frac{3}{2}-\frac{5}{2}\right)\)
A = \(-2-0+\left(2-\frac{5}{2}\right)\)
A = \(-2+\left(2-\frac{5}{2}\right)\)
A = \(-2+2-\frac{5}{2}\)
A = \(0-\frac{5}{2}\)
A = \(\frac{-5}{2}\)
\(\left(-2\right).\left(-1\frac{1}{2}\right)\left(-1\frac{1}{3}\right).....\left(-1\frac{1}{2013}\right)\)
\(=\left(-2\right).\left(\frac{-3}{2}\right)\left(-\frac{4}{3}\right)......\left(\frac{-2014}{2013}\right)\)
\(=\frac{\left(-2\right).\left(-3\right).\left(-4\right)....\left(-2014\right)}{2.3.....2013}\)
\(=\frac{2.3.4....2014\left(\text{Vì có 2014 thừa số âm }\right)}{2.3....2013}\)
\(=\frac{\left(2.3.4....2013\right).2014}{2.3....2013}\)
\(=2014\)